Residual Stand Damage Due to Timber Harvesting in PT Tunas Timber Lestari, Papua - Yuniawati; Dulsalam (Foresty Faculty of Hasanuddin University, 2020)
Timber harvesting activities can cause damage to residual stands, this can occur due to improper timber harvesting techniques. The study was conducted at one of PT Tunas Timber Lestari’s IUPHHK-HA in Papua Province. The results showed that: 1). The number of trees felled and skidded on 3 logging compartment with each of the 3 plot of observation sample has an area of 2 ha (the total area of the research is 18 ha) is 16 trees on average; 2). The average number of residual stand (trees with a diameter of ≥ 20 cm) damaged by logging is 26 trees (13.00%) per ha with details of damage to canopy of 4 trees (15.39%), broken branches of 13 trees (50.00%), the trunk wound of 2 trees (7.69%) and the collapsed/tilted of 7 trees (26.92%); 3). Damage to the residual stand in felling is caused more by the lack of skilled chainsaw operators in determining felling direction; 4) Damage to residual stands due to skidding is an average of 23 trees (9.99%) per ha, with details of 1 trees buttress (4.4%), wounds injuries of 7 trees steam (2.97) and collapsed/slanted 15 trees (65.2%); and 5). The cause of damage to the residual stand on skidding is that the skid trail has not been made and the skid tractor maneuvers too often.